2021
DOI: 10.1515/lex-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Der Europäische Master für Lexikographie 2021 an der Friedrich-Alexander-Universität Erlangen-Nürnberg

Abstract: The following report reflects on the activities of EMLex concerning eight consortium meetings, the 6th intake for Erasmus Mundus scholarships and the situation in the corona pandemic. It also gives a short overview over the international summer term which took place at the Friedrich-Alexander-Universität Erlangen-Nürnberg in 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The new variables, as the components, were aggregated by a two-step cluster analysis in SPSS 22. The log similarity value was chosen as the distance measure, and the Bayesian information criterion (BIC) was chosen as the clustering criterion [87]. Taking advantage of the automatic determination of the cluster number by the software, different cluster distributions and cluster combination occupancy ratios could be formed.…”
Section: Identification and Visualization Of Landscape Character Typesmentioning
confidence: 99%
“…The new variables, as the components, were aggregated by a two-step cluster analysis in SPSS 22. The log similarity value was chosen as the distance measure, and the Bayesian information criterion (BIC) was chosen as the clustering criterion [87]. Taking advantage of the automatic determination of the cluster number by the software, different cluster distributions and cluster combination occupancy ratios could be formed.…”
Section: Identification and Visualization Of Landscape Character Typesmentioning
confidence: 99%
“…Next, an early computation of the number of groups was performed by utilizing that indicator. By identifying the distance's biggest change between the two nearest groups throughout each stage of hierarchical clustering, the early estimation was finally improved [34]. where…”
Section: Clustering Analysismentioning
confidence: 99%
“…Various studies are available about the usage of dynamically obtained stiffness values, and a few examining static loading. [4], [5], [6], [7] No publications about performing the study on the same specimen after cyclic static loading has been found by the authors. In this research, static and dynamic experiments are performed on the same specimen -a real rotor lamination stack used in an automotive electric drive, to avoid altering the nonlinear behavior of the assembly.…”
Section: Introductionmentioning
confidence: 99%